Femoral Artery Injuries in Closed Femur Shaft Fractures: Case Report - Krishna, Sathya Vamsi; B., Sindhu; T.R, Suhas; Sumanahalli, Chandrashekar H. (The Surgery Journal, 2022)
Case 1 and 2 Two young male patients, sustained injury to the superficial femoral artery (SFA) following a closed femur shaft fracture. The arterial injuries were confirmed by computed tomography angiography and both underwent fracture fixation and on SFA exploration; a thrombosed arterial segment was noted at the fracture site, addressed with arteriotomy and thrombectomy to restore the vascularity. At 1-year follow-up, both patients had good union at the fracture site and a well-perfused limb.Conclusion Thorough clinical examination and appropriate diagnostic studies can diagnose these rare vascular injuries in closed fractures and with early vascular repair potentially limb-threatening complications can be prevented.
Keywords: closed femur shaft fracture; vascular injury; superficial femoral artery; thrombectomy; fasciotomy; intramedullary interlocking nail